Selective depletion of microglial progranulin in mice is not sufficient to cause neuronal ceroid lipofuscinosis or neuroinflammation - Terri L. Petkau; Natalia Kosior; Kathleen de Asis; Colúm Connolly; Blair R. Leavitt (Journal of Neuroinflammation, 2017)
Abstract Background Progranulin deficiency due to heterozygous null mutations in the GRN gene are a common cause of familial frontotemporal lobar degeneration (FTLD), while homozygous loss-of-function GRN mutations are thought to be a rare cause of neuronal ceroid lipofuscinosis (NCL). Aged progranulin-knockout (Grn-null) mice display highly exaggerated lipofuscinosis, microgliosis, and astrogliosis, as well as mild cell loss in specific brain regions. In the brain, progranulin is predominantly expressed in neurons and microglia, and previously, we demonstrated that neuronal-specific depletion of progranulin does not recapitulate the neuropathological phenotype of Grn-null mice. In this study, we evaluated whether selective depletion of progranulin expression in myeloid-lineage cells, including microglia, causes NCL-like neuropathology or neuroinflammation in mice. Methods We generated mice with progranulin depleted in myeloid-lineage cells by crossing mice homozygous for a floxed progranulin allele to mice expressing Cre recombinase under control of the LyzM promotor (Lyz-cKO). Results Progranulin expression was reduced by approximately 50–70% in isolated microglia compared to WT levels. Lyz-cKO mice aged to 12 months did not display any increase in lipofuscin deposition, microgliosis, or astrogliosis in the four brain regions examined, though increases were observed for many of these measures in Grn-null animals. To evaluate the functional effect of reduced progranulin expression in isolated microglia, primary cultures were stimulated with controlled standard endotoxin and cytokine release was measured. While Grn-null microglia display a hyper-inflammatory phenotype, Lyz-cKO and WT microglia secreted similar levels of inflammatory cytokines. Conclusion We conclude that progranulin expression from either microglia or neurons is sufficient to prevent the development of NCL-like neuropathology in mice. Furthermore, microglia that are deficient for progranulin expression but isolated from a progranulin-rich environment have a normal inflammatory profile. Our results suggest that progranulin acts, at least partly, in a non-cell autonomous manner in the brain.